JUSTIÇA ORGANIZACIONAL E CAPITAL PSICOLÓGICO: INFLUÊNCIA SOBRE BEM-ESTAR SUBJETIVO E ENGAJAMENTO NO TRABALHO - Januário, Marcelo Soares (2015)
There are indications that social resources of the working environment, including organizational justice, could affect ties with the work, and have shocked the levels of well-being of workers. In addition, evidence suggests that certain psychological characteristics of workers would vary positively or negatively influence the magnitude of the resources on the links with work and on well-being. Based on this evidence this study aimed to analyze the influence of organizational justice (distributive, procedures and interactional) and psychological capital on engagement at work and subjective well-being (emotional balance and life satisfaction). From the main goal, four hypotheses have been proposed: perception of organizational justice increases engagement at work (H1) and subjective well-being (H2); psychological capital was moderator of the relationship between organizational justice and subjective well-being (H3) and the relationship between organizational justice and engagement (H4), and that high levels of psychological capital would strengthen relations. The design was a cross-sectional quantitative, descriptive and non-probability sampling. From a sample of 293 workers with an average age of 38.3 (SD = 10.7) years, of which slightly more than half were women (56.3pc), coming from all regions of Brazil, predominantly in the Southeast (65.2pc) was measured with valid and accurate scales, through an online questionnaire, the organizational justice levels, psychological capital, engagement at work and subjective well-being. Two sets of multiple linear regression analysis to test the hypotheses were performed. In the first set of analyzes, the results of standard multiple linear regressions indicated that organizational justice influenced the levels of engagement at work and subjective well-being, and, in relation to engagement and emotional balance, only the interactional dimension of justice was significant predictor while distributive justice was the only significant predictor of life satisfaction. In the second set of analyzes, the hierarchical multiple linear regressions for each dimension of organizational justice, along with psychological capital and interaction term upon engagement at work and subjective well-being, they indicated that psychological capital moderated the relations of procedural justice and interactional justice on engagement at work. It was concluded from the results that the perception of being adequately remunerated for their efforts at work, participate in decisions that affect the work and be treated with respect and sincerity can influence the levels of pride and inspiration at work, engagement features, and may increase the subjective well-being levels, contributing to the prevailing experience of positive affect and positive satisfaction ratings with life. Moreover, although it is not possible to say that workers with higher levels of belief in their ability to perform their tasks and with good prospects for the future, can do without fair environments to engage in work, the results showed that these workers can suffer less influence of interactional and procedural justice to establish that bond with their work, demonstrating that these personal characteristics would act as shock absorbers given the lack of environmental resources.